IMPLEMENTASI PEMBELAJARAN MENYENANGKAN DENGAN TRIK DAN TIPS CARA MUDAH BELAJAR MATEMATIKA - Nur Hasanah; Tri Astindari; Irma Noervadila (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2023)
Mathematics is a very important subject and very useful in everyday life. But in reality it is also a subject that is feared by students in general. This is because students assume that mathematics has material that is difficult to understand because it is always related to calculations, numbers, and formulas. One way to make students happy about learning mathematics is by introducing fun math learning tricks and tips. This service is carried out in elementary schools in the areaSumberkolak obtained the result that by getting to know learning using fun math learning tricks and tips it has begun to be seen that students are starting to like mathematics from the haunted results that have been distributed to students, it is found that students who are very happy learning mathematics using tips and tricks are obtained with a percentage of 70%, who enjoy learning mathematics 18%, less happy 10% and some who are still not happy with mathematics 2%. So, it can be stated that there is an increase in interest in learning mathematics and there is a positive response from students' mindsets towards learning mathematics